PERAN PROFESIONALISME GURU DALAM MENINGKATKAN MUTU PENDIDIKAN - Hasibuan, NAsruddin (AIN Padangsidimpuan, 2013)
AbstractThe teacher as educator undertake to endow science and technology to all its pupil. Even pupil also learn to get and develop skill, exercising applying for the shake of larger ones benefit also from its teacher. Despitefully teacher also have to ready to functioned as second parent for all its pupil after parent as first parent. It’s here needed by domination of therapy hpsychology and character of human being to be able to and served precisely by all teacher. Duty of teacher very much plenty of both for related to on duty and its profession in school, liketeaching and guiding of all its pupil, drawing up needed administration, is not including effort improvement and development of science becoming its study area of under developed in order not to era, and or outside on duty which related to human duty and extramural social in general. Insulation teacher may not from growth of its society socialKeywords: Role, learn, develop skill, improve qulity